Bacterial magnetic particles improve testes-mediated transgene efficiency in mice. (1st January 2017) - Wang, Chao; Sun, Guanghong; Wang, Ye; Kong, Nana; Chi, Yafei; Yang, Leilei; Xin, Qiliang; Teng, Zhen; Wang, Xu; Wen, Yujun; Li, Ying; Xia, Guoliang
Abstract: Nano-scaled materials have been proved to be ideal DNA carriers for transgene. Bacterial magnetic particles (BMPs) help to reduce the toxicity of polyethylenimine (PEI), an efficient gene-transferring agent, and assist tissue transgene ex vivo . Here, the effectiveness of the BMP-PEI complex-conjugated foreign DNAs (BPDs) in promoting testes-mediated gene transfer (TMGT) in mouse was compared with that of liposome-conjugated foreign DNAs. The results proved that through testes injection, the clusters of BPDs successfully reached the cytoplasm and the nuclear of spermatogenesis cell, and expressed in testes of transgene founder mice. Additionally, the ratio of founder mice obtained from BPDs (88%) is about 3 times higher than the control (25%) ( p < 0.05). Interestingly, the motility of sperms recovered from epididymis of the founder mice from BPD group were significantly improved, as compared with the control ( p < 0.01). Based on classic breeding, the ratio of transgene mice within the first filial was significantly higher in BPDs compared with the control (73.8% versus 11.6%, p < 0.05). TMGT in this study did not produce visible histological changes in the testis. In conclusion, nano-scaled BPDs could be an alternative strategy for efficiently producing transgene mice in vivo .